TINGKAT KECEMASAN REMAJA PUTRI DI SMA MUHAMMADIYAH I PARE DALAM MENGHADAPI HAID - Slamet, Eko; Cahyono, Aris Dwi; Purwati, Purwati (Jurnal AKP, 2010)
Anxiety is  an situation  jiggling caused  by threat to  health,  particularly  to is  adolescent  of woman whichnot  yet  comprehended  correctness  about  menstruation,  menstruation  which  is  not  regular  to  be  accompaniedpain in bone often generate panicity andanxiety at adolescent, intention of this research is to know adolescentanxiety level of woman in SMA Muhammadiyah I Pare facing menstruation.In  this  research  the  used  is  descriptive  desain,  its  population  all  is  adolescent  of  women  in  l  SMAMuhammadiyah I Pare, by using technique total sampling, with amount of sampel 83 responder.From result ofresearch  got  at  most  natural  responder  of  anxiety  that  is  36  responder  (43,4%),  hereinafter  32  responder(38,6%)  experiencing  of  light  anxiety,  9  responder  (10,8%)  experiencing  of  heavy  anxiety,  and  at  least  6responder (7,2%) do not experience of anxiety.According  to  breakdown  of  above  showing  at  most  natural  responder  of  anxiety,  this  matter  is  enabledbecause pertained age factor is adolescent age, besides type of stressor also very is influencing anxiety level. Seeresult  of  the  research  according  to  researcher  need  the  existence  of  counseling  about  woman  reproductionspecially regarding menstruate to add knowledge and information so that can lessen anxiety.